Impact of Accounting Information Systems on Financial Transparency and Accountability of SMEs in the Industry 4.0 Era - Novta Winkey (Terbuka Journal of Economics and Business, 2024)
This study examines the impact of implementing Accounting Information Systems on the financial transparency and accountability of Small and Medium Enterprises in the Industry 4.0 era. Small and Medium Enterprises in Indonesia face challenges in financial management, particularly related to transparency and accountability, which are crucial for business competitiveness and sustainability. Using a quantitative approach, data were collected through questionnaires from 350 SME practitioners in Banten Province who meet the criteria outlined in PP No. 7/2021, utilizing convenience sampling. The analysis was conducted using Structural Equation Modeling with Partial Least Squares. The results indicate that the implementation of Accounting Information Systems has a positive and significant effect on financial transparency and accountability. These findings underscore the importance of adopting Accounting Information Systems to enhance the quality of financial governance in Small and Medium Enterprises in the digitalization era.